Prevalence and Antibiotic Susceptibility Pattern Of Uropathogens From Urinary Tract Infection Suspected Patients Visiting Tertiary Care Hospital of Nepal - Subedi, Munal; Thapaliya, Sony; Thapa, Suchitra (Amrit Research Journal, 2024)
Antibiotic resistant uropathogens is a significant problem in all patient, leading to high morbidity, poor quality of life and a limited life expectancy thus situation analysis of those pathogens is necessary. Hence, this study aims to detect uropathogens and evaluate their current antibiotic resistant pattern. Mid-stream urine samples were cultured for bacterial isolation and isolates were identified using biochemical tests. Antibiotic susceptibility testing was done using disc diffusion method. The results were analyzed using statistical software. Out of 1784 suspected cases, 182 urine samples showed significant growth. Among uropathogens, Escherichia coli was predominant followed by Klebsiella pneumoniae, Proteus mirabilis Staphylococcus aureus, Pseudomonas aeruginosa, Morganella morganii, and Acinetobacter spp. The antibiotic-resistant pattern was observed highest among K. pneumoniae and E. coli. Also, higher resistance was observed towards Cephalexin (70.3%), followed by Ceftazidime (70.2%) and Nalidixic acid (67.6%) and Cefixime (62.5%). And, a total of 46.7% (n=85) multidrug resistant isolates were detected of which 17 were identified as high risk clones. In conclusion, antimicrobial resistance among urine isolates, particularly E. coli and K. pneumoniae seem to be emerging. Therefore, antimicrobial resistance trend analysis exploring both phenotypic and molecular techniques would be helpful in intervening in antimicrobial resistance development and spread.